Implementasi Permainan Busy Jar Untuk Melatih Kognitif dan Motorik Pada Anak Usia Dini di TK Lumbung Sari - Suciari Putri, Ida Ayu Eka; Gede Anadhi, I Made; Sindu Putra , Ida Bagus Komang; Suardika , I Komang (Generasi Emas, 2024)
This study is motivated by the cognitive abilities of TK Lumbung Sari children are still lacking in learning activities, so to help children develop their cognitive abilities, a medium is needed that is used in the learning process such as busy jar. Busy jar is a tube-shaped media from plastic material which in the bottle cap there are holes of various shapes such as geometric shapes. This study aims to train cognitive in early childhood. The purpose of this study is to train early childhood self-confidence and to teach children geometric shapes, train children's fine motor skills and increase children's vocabulary in mentioning geometric shapes and colors. This study uses qualitative research methods, data collection techniques used in this study are observation and interviews. The subjects in this study were 23 students at TK Lumbung Sari. This study uses observation and interviews in collecting data.  This study shows the results where when playing busy jar students are very happy to carry out this busy jar play activity but there are some students when playing this game at the Pre-test stage there are those whose abilities have not developed, so the researcher sees the child's development at the next stage, namely the post-test stage and from the results of this simulation stage the student's ability has begun to develop so that the results of this busy jar game can be concluded that busy jar games are suitable for cognitive and motor training in children and have a positive impact received by early childhood.